Conscious While Being Considered in an Unresponsive Wakefulness Syndrome for 20 Years - Vanhaudenhuyse, Audrey; Charland-Verville, Vanessa; Thibaut, Aurore; Chatelle, Camille; Tshibanda, Jean-Flory L.; Maudoux, Audrey; Faymonville, Marie-Elisabeth; Laureys, Steven; Gosseries, Olivia (Frontiers in Neurology, 2018)
Despite recent advances in our understanding of consciousness disorders, accurate diagnosis of severely brain-damaged patients is still a major clinical challenge. We here present the case of a patient who was considered in an unresponsive wakefulness syndrome/vegetative state for 20 years. Repeated standardized behavioral examinations combined to neuroimaging assessments allowed us to show that this patient was in fact fully conscious and was able to functionally communicate. We thus revised the diagnosis into an incomplete locked-in syndrome, notably because the main brain lesion was located in the brainstem. Clinical examinations of severe brain injured patients suffering from serious motor impairment should systematically include repeated standardized behavioral assessments and, when possible, neuroimaging evaluations encompassing magnetic resonance imaging and 18F-fluorodeoxyglucose positron emission tomography.